NEEDS FOR DEVELOPMENT OF EDUCATIONAL INNOVATIVE ORGANIZATION UNDER SARABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Buaban, Areerat; Pichayakul, Thitiporn; Klangphahol, Kanreutai (Journal of Educational Review Faculty of Education in MCU, 2025)
The purpose this research article were to study the needs for development of educational innivative organization under Saraburi primary educational service area office 2. The research was quantitative with a sample group consisted of 393 administrators and teachers under Saraburi primary educational service area office 2, Samples were defined using Krejcie and Morgan and a stratified random sampling method was employed based on school size. The research instrument was a questionnaire using a 5-point Likert scale, with a reliability coefficient of .99. Data were anlyzed using frequency, percentage , mean, standard deviation and prioritization of need using the Modified Priority Need Index. The research results were found as follows:The needs for development of educational innivative organization under Saraburi primary educational service area office 2 in overall was index of 0.378. When considering individual aspect, the first priority was organizational structure, the second was the importance of personnel, the thired was personnel skills, the fourth was creative organizational climate, the fifth was effective communication, the sixth was innovation learning organization, the seventh was monitoring and evaluation of innovation and the eighth was shared vision.